TEACHING READING COMPREHENSION BY USING SKIMMING AND SCANNING TECHNIQUES TO THE TENTH GRADE STUDENTS OF SMAN 1 GELUMBANG - Marliasari, Sherly (English Education Study Program Universitas Muhammadiyah Palembang, 2017)
The objective of this research was to find out whether or not it was effective to teach skimming and scanning techniques in reading a narrative text by the tenth grade students of SMAN 1 Gelumbang. The method used experimental. The population of this study was all tenth grade students of SMAN 1 Gelumbang. The sample of this study was 60 students. It indicated that the null hypothesis (Ho) was rejected and alternative hypothesis (Ha) was accepted. It could be concluded that it was effective to teach reading comprehension by using skimming and scanning techniques to the tenth grade students of SMAN 1 Gelumbang.